Shifting Subject Positions: Experts and Lay People in Public Dialogue - Kerr, Anne; Cunningham-Burley, Sarah; Tutton, Richard (Social studies of science, 2007)
Public dialogue about science, technology and medicine is an established part of the activities of a range of charities, private corporations, governmental departments and scientific institutions. However, the extent to which these activities challenge or bridge the lay-expert divide is questionable. Expertise is contested, by the public and the community of scholars who study and/or facilitate public engagement. In this paper, we explore the dynamics of expertise and their implications for the lay-expert divide at a series of public events about the new genetics. We examine participants' claims to expertise and consider how this relates to their claims to credibility and legitimacy and the way in which these events unfolded. Using a combination of ethnographic and discursive analysis, we found that participants supplemented technical expertise with other expert and lay perspectives. We can also link participants' claims to expertise to their generally positive appraisal of genetic research and services. The colonization of lay positions by expert speakers and the hybrid positioning of lay-experts was characteristic of the consensus and conservatism that emerged. This leads us to conclude that public engagement activities will not challenge the dominance of technical expertise in decision-making about science, technology and medicine without more explicit and reflexive problematization of the dynamics of expertise therein.